INTERCULTURAL COMPETENCIES OF STUDENTS IN RELATION TO THEIR PARENT'S LEVEL EDUCATION AND FINANCIAL STATUS - Marija Tomić; Brane Mikanović (Istraživanja u Pedagogiji)
Intercultural competences are key skills for living in modern society, as we are constantly faced with the need to adapt and cooperate with people from different cultures. In order to adapt successfully, it is necessary to develop new forms of behavior. Basic qualities such as openness, tolerance and communication skills become essential for navigating such an environment, and these skills should be learned from an early age. An upbringing that helps children live and work in multicultural environments contributes to their personal development, but also to the progress of the wider social community. Possessing intercultural competences allows individuals to navigate in different ethnic, religious and national groups, which is crucial for the progress of society as a whole. This paper investigates how elementary school students assess their intercultural competences, taking into account the level of education of their parents and their financial status. The data were collected using a specialized scale of selfassessment of intercultural competences. The results show that the difference in the level of self-assessment of intercultural competences is not statistically significant in relation to the level of education of parents or their financial status. These results also open space for further research in order to understand the causes of the obtained results.